The capacity of community organizations in maintaining cultural entities as character values of Pasuruan society - Rizqi, Ascosenda Ika; Kartika, Rika; Habibah, Siti Maizul (Digital Theory, Culture & Society, 2023)
Local wisdom that has become a character building since several decades ago seems to be lost, in order to maintain this character, a community organizing capacity is needed that can be a bridge between the community and the government and a bridge between the community and the community, The method used in this paper uses ethnographic studies. The celebration of Praonan and Haul Kyai is a special attraction in maintaining the traditions of regional entities that are a source of pride.